2007
DOI: 10.1002/app.25519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow history on poly(vinylidine fluoride) crystalline phase transformation

Abstract: This study was devoted to the effect of extensional flow during film extrusion on the formation of the b-crystalline phase and on the piezoelectric properties of the extruded poly(vinylidine fluoride) (PVDF) films after cold drawing. The PVDF films were extruded at different draw ratios with two different dies, a conventional slit die and a two-channel die, of which the latter was capable of applying high extensional flow to the PVDF melt. The PVDF films prepared with the two-channel die were drawn at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
(24 reference statements)
1
12
1
Order By: Relevance
“…According to the reference works [43,44] and our experiment, stretching ratio over 3 is good enough for later poling. After stretching and/or poling process, α-phase will transform into β-phase.…”
Section: Resultsmentioning
confidence: 99%
“…According to the reference works [43,44] and our experiment, stretching ratio over 3 is good enough for later poling. After stretching and/or poling process, α-phase will transform into β-phase.…”
Section: Resultsmentioning
confidence: 99%
“…, where: A α and A β -are the heights of the peaks at 764 and 840 cm −1 , respectively, and the coefficient 1.26 represents the ratio of the absorption coefficients at 764 and 840 cm −1 [9][10][11].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…PVDF is known to exist in at least four crystal forms, which are designated α, β, γ, and δ. The crystalline structure and the formation of the piezoelectric β polymorph in particular have been well explored in the case of PVDF films 6–9. Although the nonpolar α phase is usually formed during crystallization from the melt or in solution‐cast films, the polar β phase can be created by mechanical deformation of α‐phase material.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, the β phase can be formed by mechanical deformation of α‐phase material, and several researchers have attempted to find the optimal drawing parameters for producing PVDF films with a high content of β‐phase crystallites. It has been found that the formation of a necking region during drawing is advantageous, and the draw ratio (λ) as well as the draw rate should be as high as possible for maximum α‐to‐β transformation to take place 7, 8. The drawing temperature for maximum α‐to‐β transformation is in the range of 80–90°C.…”
Section: Introductionmentioning
confidence: 99%